Can Sustainability Report Disclosure Influence the Valuation of Insurance Companies? - Agung, Chris Petra; Dewi, Vera Intanie; Kesaulya, Feby Astrid; Samuel, Samuel; Putri, Nabilla Ditya (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
The Association of Indonesian Life Insurance Companies (AAJI) has encouraged insurance companies to apply environmental, social, and governance (ESG) principles in their business activities. However, insurance companies in Indonesia generally have not fully implemented sustainability principles in their operational activities due to the uncertainty of increased fi rm values after the implementation. One way to communicate the company's sustainability steps is through the sustainability report (SR), which the Financial Services Authority (OJK) obliged. Although the guidelines had already been prepared in 2021, the depth and breadth of the disclosure depend on each company. Previous studies found that several factors aff ect SR disclosure. This study aims to investigate the role of profi tability and fi rm size as determinants of SR disclosure and the eff ect of SR disclosure on company value. The sample of this study was 15 insurance companies listed on the Indonesia Stock Exchange (IDX) that routinely published SR during the 2021-2023 period. The data was processed using Partial Least Squares - Structural Equation Modelling (PLS-SEM) through SmartPLS ver—3 software. The results of this study show that (1) profi tability has a positive eff ect on SR disclosure, (2) company size has a positive eff ect on SR disclosure, and (3) company size has a positive eff ect on company value.